Characterization of patients diagnosed with drug-induced liver injury - Itay Ashkenazi; Yoav Lurie; Ariel Kenig; Shoshana Zevin; Ina Gafanovich; Elad Resnick; Shimon Shteingart; Tali Bdolach-Abram; David E Katz (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
Introduction and Objectives: Drug-induced liver injury (DILI) is the most common cause of acute liver failure in the USA, and a major cause of medication discontinuation. However, DILI is often under-diagnosed, primarily due to the lack of agreed upon diagnostic criteria and limiting coding nomenclature.  Materials and methods: We conducted a retrospective observational analysis of demographic, clinical, and laboratory data for 55 patients hospitalized in an Israeli tertiary care medical center between 2005-2017 and diagnosed with DILI. Results: We identified 55 patients hospitalized with DILI over 12 years. DILI was associated with female gender and older age. Hepatocellular injury was the most common type of liver injury (49.0%). Common manifestations included fever (41.8%), weakness (41.8%) and jaundice (34.5%). The major offending drug group was antibiotics (35.0%) with amoxicillin and clavulanate being the most common drugs (7.2%). Most cases were caused by drugs administered orally (84%), while cholestatic injury was associated with intravenous administration. De Ritis ratio (AST/ALT) was above 1.0 in 75% of cases.  Conclusions: Most DILI was caused by oral antibiotics. The incidence of DILI in our study was low, possibly due to under-diagnosis or misclassification. The adoption of the updated international classification of disease 10th edition  may improve reporting rates. Utilization of the De Ritis ratio may help to differentiate between DILI and viral hepatitis.